The Recreation and Leisure Pursuits of Employed Adults with Visual Impairments in Nigeria: Part 1. (January 2015) - Kelly, Stacy M.; Ajuwon, Paul M.; Wolffe, Karen E.
Introduction: This qualitative study explored the recreation and leisure activities of employed Nigerians with visual impairments. Methods: A questionnaire was developed that examined the work, recreation, and leisure activities of adults with visual impairments. The sample included 172 adults with visual impairments living and working in Nigeria. Participant responses to the open-ended survey questions about recreation and leisure activities are presented in this article. Results: Although most participants (89%) reported engagement in some sort of recreation or leisure activity on a regular basis, the vast majority of recreation and leisure activities reported were sedentary (69%) or solitary in nature such as listening to the radio, watching television, reading, or cooking. Participants identified the lack of personal funds or time, facilities, and adapted equipment as challenges to their recreation and leisure participation. Transportation issues and environmental barriers, discrimination, and inadequate assistance or training of human supports were also included in the challenges reported. Discussion: Choices for recreation and leisure involvement were severely limited for participants. Active and community-based recreation and leisure offerings were virtually nonexistent. Although the respondents were employed, their economic status as workers was not adequate to support their engagement in a variety of recreation and leisure activities. The underlying turmoil of social, political, and economic issues described by participants was a highly restrictive obstacle. Implications for practitioners: Practitioners and other stakeholders in developing countries are encouraged to intervene in the remediation of extrinsic and intrinsic barriers to recreation and leisure participation on behalf of their students and clients. Public awareness efforts, professional development courses, and disability-specific skill training programs are essential components in the improvement of the overall life satisfaction of people with visual impairments.